Intraventricular Vancomycin In Pediatric Patients With Cerebrospinal Fluid Shunt Infections - Al-Jeraisy, Majed (Pediatric Pharmacy Advocacy Group, 2004)
OBJECTIVES: To determine: 1) the range and magnitude of vancomycin trough cerebrospinal fluid (CSF) concentrations following intraventricular (IVT) vancomycin; 2) any correlation between patient demographic and CSF vancomycin concentrations; and 3) eradication and complications rates following IVT vancomycin. METHODS: Medical records of pediatric patients with shunt infection who received IVT vancomycin during a 12 month period were reviewed. Demographic, microbiological data, IVT/intravenous (IV) vancomycin dosing, concomitant antibiotics, CSF and serum vancomycin concentrations, and CSF drainage output were recorded. RESULTS: Seventeen patients ages 4 months to 17 years were hospitalized for shunt infection. Staphylococcus epidermidis (n=12) was the predominant organism. Sixteen patients received 10 mg, and one patient received 5 mg of IVT vancomycin for 3–23 days. All but one received concurrent IV vancomycin. The mean maximum trough CSF vancomycin concentration noted for 16 patients who recieved 10 mg of IVT vancomycin was 18.4±21.8 μg/mL (range: between 0.4 to 187.3 μg/mL). All four adolescents ≥25 kg had CSF vancomycin concentrations ≤5 μg/mL, three of four infants/children between 10.1 and 24.9 kg had trough CSF vancomycin concentrations between 10–20 μg/mL, and five of nine infants <10 kg had CSF concentrations >20 μg/mL. All organisms were successfully eradicated. One patient developed chronic eosinophilia presumed related to elevated CSF vancomycin concentrations (187 μg/mL). CONCLUSIONS –: The combination of IVT and IV vancomycin effectively eradicated CSF shunt infections. CSF vancomycin concentrations are highly variable and poorly correlated with age and CSF output. Following a 10 mg IVT vancomycin dose, CSF concentrations appear to be lower in older children and elevated in infants/young children. One infant experienced a complication related to an elevated CSF vancomycin concentration; hence, therapy must be individualized, using CSF trough vancomycin concentrations.